CIPP evaluation learning development model in vocational laboratories based on ISO 9001: 2008. Issue 4 (April 2020) - Mukhidin, M; Kustiawan, I; Suartini, T; Hasan, B; Sukandar, A
Abstract: The purpose of this study is to evaluate the learning process in vocational high school laboratory certified ISO 9001:2008 using CIPP (Context Input Process Product) learning model. We conducted the combination of quantitative and qualitative research method in vocational high schools, West Java area. The instruments for collecting data consist of paper test, observations and discussions with the principals, teachers, students, and industrial representatives. The results showed that learning model is very appropriate because of fulfilling ISO requirements, that is, standards for input, process, product, infrastructure, and evaluation. This model can be used as a learning model by teachers in vocational high school laboratories.